2020
DOI: 10.1016/j.ijid.2020.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Murine typhus. How does it affect us in the 21st century? The epidemiology of inpatients in Spain (1997–2015)

Abstract: The aim of this study was to analyze the epidemiological impact of murine typhus in patients who required hospitalization in the National Health System (SNS) in Spain between 1997 and 2015. Background: Murine typhus (MT) is a zoonosis caused by Rickettsia typhi. MT is transmitted from rats, cats, dogs, and opossums to humans by their fleas. The clinical picture is characterized by headache, fever, rash, and liver function alteration. The prevalence of MT is considered underestimated since most cases are mild a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…In our work, the methodology applied is similar to use in previous studies in acute 18 and chronic infectious diseases 19 . Data were obtained from the Minimum Basic Data Set (CMBD in Spanish) recorded in each inpatient in a public hospital of the national health system.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, the methodology applied is similar to use in previous studies in acute 18 and chronic infectious diseases 19 . Data were obtained from the Minimum Basic Data Set (CMBD in Spanish) recorded in each inpatient in a public hospital of the national health system.…”
Section: Discussionmentioning
confidence: 99%
“…MT is ubiquitous in developing countries, with seroprevalence rates of 6.5% and 5.4% in northern Vietnam (36) and southern India (18), respectively. In addition, the incidence of MT has temporarily decreased, but has become a problem in developed countries such as the US (California and Texas) (68), Greece (9), and Spain (10,11). One possible reason for the increase in MT in California and Texas is the improved disease recognition by clinicians through local epidemiological studies (8,37).…”
Section: □Discussion□mentioning
confidence: 99%
“…MT is distributed globally and is endemic in warm urban or coastal regions, where rats or cats, the reservoirs of R. typhi , tend to inhabit; however, epidemiological characteristics often differ from region to region (1). Reports from industrialized countries, such as the US (68), Greece (9), and Spain, (10,11) have accumulated. Epidemiological studies from the US have indicated that MT is endemic not in urban areas but in suburban areas (6,8), potentially due to a new transmission cycle between fleas and reservoirs, such as opossums (12,13).…”
Section: □Introduction□mentioning
confidence: 99%
“…The fact that brucellosis has been identified as the primary diagnosis in more than 67% of cases indicates a much higher diagnostic suspicion than in other infections that cause fever of intermediate duration [ 21 , 22 ]. The mean stay of individuals with a secondary diagnosis is significantly longer than that in the primary forms.…”
Section: Discussionmentioning
confidence: 99%